2008
DOI: 10.1111/j.1365-2133.2008.08601.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of vitamin D supplementation for winter-related atopic dermatitis in Boston: a pilot study

Abstract: In this study, 42AE5% of patients with GAE had ichthyosis, which is much higher than in healthy controls (Table 2). However, the other 57AE5% of patients with GAE did not have ichthyosis, suggesting that other factors must be studied further. Atopic diathesis is associated with dry skin; however, our results did not show a higher percentage of patients with atopic diathesis in the GAE group (Table 2).In contrast to reports in the literature, the GAE group in our study contained more women than men. 1 The gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
131
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 11 publications
(26 reference statements)
5
131
1
4
Order By: Relevance
“…In vitro, calcitriol-stimulated dendritic cells can promote the development of Treg cells [10] and calcitriol directly enhances expression of IL-10 by Th cells [11]. Acquired vitamin D deficiency has been correlated to increased prevalence and severity of inflammatory immune-mediated diseases, such as rheumatoid arthritis [2,36], multiple sclerosis [37,38], but also is discussed in context with allergic asthma [4] and atopic dermatitis [5,39]. Furthermore, VDR haplotypes with putatively reduced effector function correlate with increased incidence of multiple sclerosis [40] and allergic asthma [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, calcitriol-stimulated dendritic cells can promote the development of Treg cells [10] and calcitriol directly enhances expression of IL-10 by Th cells [11]. Acquired vitamin D deficiency has been correlated to increased prevalence and severity of inflammatory immune-mediated diseases, such as rheumatoid arthritis [2,36], multiple sclerosis [37,38], but also is discussed in context with allergic asthma [4] and atopic dermatitis [5,39]. Furthermore, VDR haplotypes with putatively reduced effector function correlate with increased incidence of multiple sclerosis [40] and allergic asthma [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, the severity of atopic dermatitis was independently influenced by the serum 25(OH)D levels and by food allergen sensitization. Promising results of improved eczema symptoms have been found using oral vitamin D supplementation (1000 IU vitamin D for 30 days) in children between 2 and 17 years in two double-blinded placebo-controlled studies performed during wintertime [38,39].…”
Section: Vitamin D and Atopic Dermatitismentioning
confidence: 99%
“…This could be of particular value as it overcomes the compliance problem that is commonly faced while using phototherapy [24], and has a higher safety profile when the side effects of phototherapy [25], or even topical steroids [26] are considered. The use of oral calcidiol in the management of AD has been proven before to be successful [9,22,[27][28][29][30]. Two studies [29,30] enrolled pediatric patients who had a history of AD, and both studies showed that eczema area and severity index (EASI) was decreased after calcidiol supplementation.…”
Section: Groupmentioning
confidence: 99%
“…The use of oral calcidiol in the management of AD has been proven before to be successful [9,22,[27][28][29][30]. Two studies [29,30] enrolled pediatric patients who had a history of AD, and both studies showed that eczema area and severity index (EASI) was decreased after calcidiol supplementation. Similar findings were shown by the others [9,22,27,28] but with using the SCORAD.…”
Section: Groupmentioning
confidence: 99%